Light scattering on phonons in quasi-one-dimensional antiferromagnet CsFeCl3·2H2O induced by magnetic ordering: Магнетизм - Kurnosov, V. S.; Pashkevich, Yu. G.; Peschanskii, A. V.; Fomin, V. I.; Yeremenko, A. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
The appearance of new phonon lines in the Raman spectrum of the quasi-one-dimensional antiferromagnet CsFeCl3·2H2O as a consequence of magnetic ordering with a change of the unit cell volume was detected experimentally. An analysis of the possible mechanisms that might lead to the observed spectral features is done. A new mechanism of inducing Raman scattering on phonons from the boundary of the paramagnetic Brillouin zone is hypothesized.